2018
DOI: 10.1111/fog.12263
|View full text |Cite
|
Sign up to set email alerts
|

Habitat analysis of the commercial tuna of the Eastern Tropical Pacific Ocean

Abstract: We have extracted information on the habitats of bigeye (Thunnus obesus), skipjack (Katsuwonus pelamis) and yellowfin (Thunnus albacares) in the Eastern Tropical Pacific Ocean by matching the spatial‐temporal distribution of catch and effort of purse seine and longline fleets collected by the Inter‐American Tropical Tuna Commission with oceanographic conditions and subjecting the matched data to Quotient Analysis and General Additive Models (GAMs). These analyses yielded the following results. The habitats def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 38 publications
0
22
1
Order By: Relevance
“…These findings are in contrast to those of Hu et al (2018) [19], who found that hypoxic layer depths, rather than temperature-related conditions and SSHAs, were most useful for laterally demarcating preferred skipjack and bigeye habitats in the ETP. There are several potential reasons for these differences.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…These findings are in contrast to those of Hu et al (2018) [19], who found that hypoxic layer depths, rather than temperature-related conditions and SSHAs, were most useful for laterally demarcating preferred skipjack and bigeye habitats in the ETP. There are several potential reasons for these differences.…”
Section: Resultscontrasting
confidence: 99%
“…Quantification of habitat preferences was done using quotient analysis, which determines whether a given environmental condition is preferred, tolerated, or avoided by a certain species based on how frequently that species appears within that condition (e.g., [19,38,52]). The steps involved in the quotient analysis performed here are as follows:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations